2023
DOI: 10.1177/03008916231212382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low skeletal muscle mass in oropharyngeal cancer patients treated with radical chemo-radiotherapy: A mono-institutional experience

Chiara L. Deantoni,
Aurora Mirabile,
Anna Chiara
et al.

Abstract: Aims: Low skeletal muscle mass index (SMI) has recently emerged as an independent prognostic factor in oncological patients and it is linked with poor survival and higher treatment toxicity. The present study aims to determine the possible impact of low SMI on survival and acute toxicity in oropharyngeal patients. Methods: Seventy-six patients with locally advanced oropharyngeal squamous cell carcinoma (stage III-IVC) were treated in our institution with Helical TomoTherapy® (HT - Accuray, Maddison, WI, USA) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…And second, Deantoni et al reported that the survival analysis of 65 patients (47 normal SMI and 18 low SMI), those with a follow-up period of over six months, revealed that the median OS was significantly longer in normal SMI (46.2 vs 40.3 months, HR 0.27, 95% CI 0.08-0.92, p-value 0.035) compared to low SMI group. 1 Similar significant disparities were also seen in patients with a lower nodal burden (N0-N2a) and a supposedly more favorable prognosis (median 46 vs 43 months, HR 0.17, 95% CI 0.04-0.79, p-value 0.02). However, upon close analysis of Figures 1 and 2, it is evident that both the low and normal SMI groups failed to achieve the sufficient number of deaths (⩾50%) required to calculate median OS times for each group.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…And second, Deantoni et al reported that the survival analysis of 65 patients (47 normal SMI and 18 low SMI), those with a follow-up period of over six months, revealed that the median OS was significantly longer in normal SMI (46.2 vs 40.3 months, HR 0.27, 95% CI 0.08-0.92, p-value 0.035) compared to low SMI group. 1 Similar significant disparities were also seen in patients with a lower nodal burden (N0-N2a) and a supposedly more favorable prognosis (median 46 vs 43 months, HR 0.17, 95% CI 0.04-0.79, p-value 0.02). However, upon close analysis of Figures 1 and 2, it is evident that both the low and normal SMI groups failed to achieve the sufficient number of deaths (⩾50%) required to calculate median OS times for each group.…”
supporting
confidence: 52%
“…We commend Deantoni et al 1 for their effort to determine whether low skeletal muscle mass index (SMI) has any impact on the survival and acute toxicity outcomes of 76 stage III-IVC oropharyngeal squamous cell carcinoma (OPSCC) patients treated with Helical TomoTherapy® and concurrent platinum-based chemotherapy. In this study, 20 patients (26%) had low pretreatment SMI according to Chargi definitions, determined by measuring the cross-sectional area at C3 vertebra level.…”
Section: Tj Tumori Journalmentioning
confidence: 99%